Reticulations : Jean-Luc Nancy and the Networks of the Political - Armstrong, Philip, 1962- (Book collections on Project MUSE., 2009)
Significantly advancing our notion of what constitutes a network, Philip Armstrong proposes a rethinking of political public space that specifically separates networks from the current popular discussion of globalization and information technology. Analyzing a wide range of Jean-Luc Nancy's works, Reticulations shows how his project of articulating the political in terms of singularities, pluralities, and multiplicities can deepen our understanding of networks and how they influence community and politics. Even more striking is the way Armstrong associates this general complex in Nancy's writin.